1997
DOI: 10.1093/ageing/26.6.493
|View full text |Cite
|
Sign up to set email alerts
|

A simple and efficient urine sampling method for bacteriological examination in elderly women

Abstract: Aim: to determine how collecting urine voided directly into a container compares with urine obtained by suprapubic aspiration. Method: urine samples were collected in a sterile recipient placed in the toilet or in the bed-pan during voiding, after the vulval region had been cleaned by water. These samples were compared with samples of the same urine obtained by suprapubic aspiration. The samples were examined for pyuria and bacteriuria. Applying the Kass criteria on the voided urine specimen and assessing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…This proved to be a reliable method of collecting urine samples from incontinent patients. 18,19 All urine samples were collected in sterile bowls.…”
Section: Methodsmentioning
confidence: 99%
“…This proved to be a reliable method of collecting urine samples from incontinent patients. 18,19 All urine samples were collected in sterile bowls.…”
Section: Methodsmentioning
confidence: 99%
“…The definition of UTI, proposed by the Centre for Diseases and Prevention, includes the presence of two or more of the following symptoms: fever, pain related to voiding, delirium, reduced general condition, new or worsened urinary incontinence or urinary frequency, foul-smelling urine or muddy and concentrated urine [17]. Given this, there is a pervasive and persistent belief that urinary tract infection in older people presents with non-specific symptoms of lethargy, malaise, and anorexia, despite being demonstrated to be untrue almost 30 years ago [18].…”
Section: Presentation Of Utimentioning
confidence: 99%
“…Evidence suggested that in this population group, urine collected in a sterile container during normal voiding after cleaning the pere‐urethral region with water is a reliable method. Specimens obtained from urethral catheterization were not recommended because of the potential for introducing infection during the process 17 …”
Section: Urinalysismentioning
confidence: 99%